2017
DOI: 10.22201/fca.24488410e.2018.984
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of millennials for a pictorial scale: An opportunity to engage younger generations to participate in research studies

Abstract: Preferencias de millennials por una escala con pictogramas: una oportunidad para interesar a jóvenes a participar en investigaciones

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, they are a more effective means of representing and conveying a meaning that helps schoolchildren of these ages to give a response (D€ oring et al, 2010). Likewise, previous studies revealed their preferences for a pictorial scale because they consider it friendlier, clearer and faster to complete (De La Cabada et al, 2017).…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, they are a more effective means of representing and conveying a meaning that helps schoolchildren of these ages to give a response (D€ oring et al, 2010). Likewise, previous studies revealed their preferences for a pictorial scale because they consider it friendlier, clearer and faster to complete (De La Cabada et al, 2017).…”
Section: Discussionmentioning
confidence: 77%